Grey Markets Formation Emanating from Economic Fluctuations and Customs Gaps (Case: Samsung Home Appliances) - Faranak Salehi; Nader Gharibnavaz; Aidin Salamzadeh (‫مدیریت بازرگانی, 2023)
Objective Grey markets are unofficial markets where economic players indulge in trading securities and other commodities. They are shaped whenever a suspended stock or commodity, neither purchased nor sold by players, is brought to the market. Such commodities would be traded even before the official trading initiates. The issue is prevalent in developing and emerging markets. Accordingly, this study seeks to explore the formation of grey markets resulting from economic fluctuations and customs gaps, with a specific focus on the Samsung home appliances market in Iran.